A study of the relationship between characteristics of secondary school principals and their level of computer use - Afshari, Mojgan; Abu Bakar, Kamariah; Wong, Su Luan; Foo, Say Fooi; Abu Samah, Bahaman (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
Principals have a major responsibility for initiating and implementing school change through the use of information and communications technology and can facilitate complex decisions to integrate them into learning, teaching and school administration. However, there is less information about the current status of ICT use by principals, their perceived competence in it, and their computer access. This paper will report on these issues from an analysis of data gathered from a survey of secondary school principals in Tehran, Iran. The findings indicated that principals spent a few times a week working on their computers. Also, factors such as age, administrative experience, training hours, high level of computer access and computer competence contributed significantly to the level of computer use by principals. It was suggested that, considerable ongoing, professional development opportunities need to be provided for principals to fulfill their role as technology leader.